Transferência de fósforo em pequenas bacias hidrográficas com predomínio de sistema plantio direto precário - Alvarez, Jimmy Walter Rasche (2014)
Agricultural activities generate impacts on the environment and require constant study and monitoring to enhance our understanding about the ways and degree of contamination resulting therefrom. The main objective of this work was to study the dynamics of transference and transformation of P in the soil, sediment and water in two small watersheds (SW), one with 142.6 ha (SW140) and another with 78.2 ha (SW80), as well as to generate information that could relate the nature of P with the mineralogy of the soil of the basin and its position in the landscape. The specific objectives were as follows: i) to characterize qualitative and quantitatively the forms of phosphorus in the sediment and relate them to soil characterization, ii) to determine the proportion and nature of mineral components in the sediment in order to identify its function in the process of pollution of water and soil, and iii) to check for differences in the transfer of phosphorus from soil to water courses between rainfall events and between sampling periods. The work was divided into three parts: i) physical-hydric and chemical characterization of two small watersheds with emphasis on quantification and qualification forms of phosphates that can be transferred to surface waters; ii) forms of phosphorus present in the water course during rainfall events, and iii) forms of phosphorus present in sediments sampled employing continuous collectors in the water course. It was noted that there are problems between agricultural use and environmental preservation areas, which have worsened since the start of monitoring (2009). Soybean is the main crop in the SWs. However, there is little application of agronomic knowledge in the SWs to improve the productivity of crops or pasture. This is evidenced by data: low soil pH, presence of exchangeable aluminum, low phosphorus, soil compaction in the 5-20 cm layer, erosion caused by planting on the slope direction, lack of soil cover and mismanaged no-till system. The soils of SWs present predominance of 1:1 clay minerals (kaolinite), however, the 2:1 clay minerals are also present, mainly in the lowlands. Due to low phosphorus in crops as a result of poor application of phosphate fertilizers, all areas studied (crops, pastures and forests) may be responsible for diffuse pollution of water courses. The phosphorus index (PI) of Alabama was the best predictor of potential vulnerability to P loss in the small watershed, however the IP of Nebraska could predict what would happen if it applied large amounts of phosphorus in agricultural areas of small watersheds. The amount of total P lost in SWs is low. However , much of the lost P is labile and moderately labile, which may produce eutrophication of water if the phosphate adsorbed to sediments reach lentic environments that allow desorption of P. In SW80 there is less loss of P in its different forms than in SW140. Similarly to soil, sediment mineralogy of SWs shows predominance of 1:1 clay mineral (kaolinite), but there are also present 2:1 clay minerals. The sediment of SW80 contains more 2:1 clay minerals than that derived from the SW140. Although there is a low level of phosphorus in soils under crops, it occurs P concentration in the sediment, mainly in the forms of P present in the labile and organic fractions.